2018
DOI: 10.5194/acp-2018-779
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Quantifying primary and secondary humic-like substances in urban aerosol based on emission source characterization and a source-oriented air quality model

Abstract: <p><strong>Abstract.</strong> Humic-like substances (HULIS) are a mixture of high molecular weight, water-soluble organic compounds that are widely distributed in atmospheric aerosol. Their sources are rarely studied quantitatively. Biomass burning is generally accepted as a major primary source of ambient humic-like substances (HULIS) with additional secondary material formed in the atmosphere. However, the present study provides direct evidence that residential coal … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 1 publication
0
10
0
Order By: Relevance
“…high-MW HULIS (Li et al, 2019). We also observe a decrease in mean molecular weight peak density in urban samples from winter to summer that is believed to be attributed to fragmentation during more intense photooxidation in summer Hand et al (2019); Jimenez et al (2009), for emission sources that do not change drastically between the two seasons.…”
Section: Molecular Weight (Mw)mentioning
confidence: 60%
“…high-MW HULIS (Li et al, 2019). We also observe a decrease in mean molecular weight peak density in urban samples from winter to summer that is believed to be attributed to fragmentation during more intense photooxidation in summer Hand et al (2019); Jimenez et al (2009), for emission sources that do not change drastically between the two seasons.…”
Section: Molecular Weight (Mw)mentioning
confidence: 60%
“… Emami and Hopke (2017) have shown that adding gases to a typical PMF data set provides additional source resolution and reduces rotational ambiguity. Li et al (2019b) provided a better resolution of PM 2.5 in Beijing by adding gases, OC/EC IMPROVE thermal fractions, and water-soluble OC and HULIS. Thus, including additional species in the data set can add to the quality of the source apportionment.…”
Section: Perspectivesmentioning
confidence: 99%
“…ous studies have identified that HULIS has both direct emission sources from biomass burning, marine aerosols, and soil resuspension and indirect contribution from secondary formation (Graber and Rudich, 2006;Hoffer et al, 2006;Lin et al, 2010;Yan and Kim, 2017). Recently, residential coal combustion was suggested as an important source of HULIS during cold seasons (Tan et al, 2016;Voliotis et al, 2017;Li et al, 2019). Besides HULIS, biological aerosols (e.g., bacteria, algae, pollen, spores, fungi, plant debris, and animal tissue) are another important sources of BrC (Després et al, 2012;Pöhlker et al, 2012).…”
Section: Introductionmentioning
confidence: 99%